PENGARUH PERENDAMAN JAGUNG DAN SUBSTITUSI TEPUNG TEMPE TERHADAP NILAI GIZI DAN SIFAT SENSORIS BERAS JAGUNG INSTAN - Nur Aini; V. Prihananto; S. Joni Munarso (Faculty of Agricultural Technology, University of Jember, 2011)
Processing corn into flour will produce byproducts of corn grits as a potential source of instantcorn rice. Modification of seed soaking in the manufacture of corn starch can alter the characteristics of the product. Efforts to increase the protein content in rice can be done in an instant corn flour substitute tempeh. The study aims to determine 1) the influence of soaking corn and soybean meal proportion of chemical and sensory properties of instant corn rice, and 2) determine a combination of soaking corn and the proportion of soybean flour that produces the best chemical and sensory properties of instant corn rice. This research used Randomized Design Group with two factors and three replications. Factor is tested is the process of soaking the seeds in the manufacture of white corn flour; that is, without soaking (P1) and a 24-hour soaking (P2), as well as variations in tempeh flour substitution (T) which consists of five levels, namely 0% (T0); 10 % (T1); 20% (T2); 30% (T3) and 40% (T4). The results showed the best of instant corn rice products is treatment combination of 20% soybean flour substitution and with 24-hour soaking (P2T2). The product has a soluble protein content 1.22% (bk), 2.76% fat content (bk), water content 6.98% (bk); carbohydrate 77.33%, with 2.44 color (yellow), texture 1 , 62 (a bit fluffier), a sense of 1.73 (rather good), corn aroma 2.11 (feeling) and the 2.38 level preferences (likes).Keywords: instant corn rice, soybean flour, soaking